(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper critically examines the issue of insider trading in the Indian securities market, focusing on the regulatory challenges, the existing legal framework, and the broader economic implications. The SEBI (Prohibition of Insider Trading) Regulations, 2015, form the core of this analysis, assessing their efficacy in deterring insider trading and upholding market integrity. Through a detailed review of landmark judicial cases such as Rakesh Agrawal vs. SEBI and Hindustan Lever Limited vs. SEBI, the paper highlights the importance of judicial interpretations in shaping the enforcement landscape and ensuring fairness. The economic analysis addresses how insider trading disrupts market efficiency, undermines investor confidence, and distorts resource allocation, supported by empirical evidence and case studies. Based on these insights, the paper proposes a series of policy recommendations aimed at enhancing the legal framework, strengthening enforcement mechanisms, improving corporate governance, utilizing technological advancements, fostering international cooperation, and increasing market transparency. These recommendations are designed to create a fair and transparent market environment, bolstering investor trust and contributing to sustainable economic growth. By integrating legal and economic perspectives, this study provides a comprehensive approach to tackling the multifaceted challenges posed by insider trading in India.